THE PERFORMANCE OF THE SHELL AND TUBE COUNTER FLOW HEAT EXCHANGER GASES FOR AGRICULTURAL DRYERS - Dandung Rudy Hartana; Eka Yawara; Daru Sugati; Amat Agus Salim (KURVATEK, 2022)
Abstract—One of the important post-harvest processes of rice is drying. Drying is divided into two, namely natural drying (using sunlight) and artificial drying (using tools). In this study drying utilizes heat from a biomass furnace and a configuration of heat exchanger pipes. Where the utilization of heat and the configuration of heat exchanger pipes in the design can increase thermal efficiency because the exhaust hot air mixed with smoke can still be used for drying. The configuration of the heat exchanger pipe greatly influences the expected moisture content level. The purpose of this study was carried out to determine the performance of the shell and tube counter flow heat exchanger for agricultural dryer gases with a heat source from biomass and to find the effect of the configuration of the heat exchanger pipe arrangement on the working process of the drying machine. This research is an experimental test of the performance of heat exchange pipes with a heat source from a biomass furnace. The exchange pipe performance parameters that must be known are temperature and time. The method used in this study refers to experimental and descriptive methods, namely research conducted in a systematic, factual and accurate manner. The results of this study are that the heated air flow rate affects LMTD, heated air outlet temperature, heat transfer coefficient, and efficiency, with variations in the heated air flow rate of 0.11 kg/s, 0.16 kg/s, 0.20kg/s, 0.24kg/s. Highest efficiency of 94% at a heated air flow rate of 0.24 kg/s. and the smallest efficiency of 74% is found in the value of the heated air flow rate of 0.11 kg/s. Keywords : dewatering, biomass, pipe configuration, heat exchanger pipe